(3eSGFd CQeS (B( (3gQeS (B) (3aj SQ GdNdjbIs - (3GdMcje gQeS , gQeS GdgQGeSIs
(3ChdgG (B:s
(3Gdbhd Ydi Ydd Jchjf GdfHGJ hceG bdJ Ydi GdGLSGO GdUe GYhGf GdJi gi eYdbI HJUQja GdGReGf s
(3BNQgG (B:s
(3jchf ef WjagG GdTLQ hjOaY GdZdjX Edi NGQLg dbdI GJUGdg aEPG GUGHg HQO GdghG CLeOg aUGQ bThQkG s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3GdeNWhW ef cJGH gQeS GdLGeY ddCTjGA GdPi aSQg HdjfGS GdMcje UGMH GdWdSeGJ hJQLeI CHh ESMGbs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs